PROFILE CHARACTERISTICS OF ORGANIC RED GRAM FARMERS OF DRY LAND AREAS OF KARNATAKA - K.B. SUNEETHA DEVI, AKKAMAHADEVI NAIK, M. SREENIVASULU, I. SREENIVASA RAO (The Journal of Research, PJTSAU, 2017)
India is a country of village comprising of 5,80,781 villages. Rural India has 73.60 per cent of the population. This population is dependent on agriculture and allied activities for its livelihood. Agriculture is the primary sector of Indian economy. Apart from being the mainstay of nearly three fourth of the population, it contributes 32 per cent to the Gross Domestic Product (GDP) and 16 per cent ofthe total exports come from agriculture sector. India has golden history of ancient agriculture and has the credit of having contributed ancient agriculture practices to other parts of the world over the years.